2016
DOI: 10.1111/jai.13134
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fish length and assessing behaviour in a high-biodiversity reach of the Upper Yangtze River using an acoustic camera and echo sounder

Abstract: Summary In the past decade improved acoustic hard‐ and software have enabled estimations of abundance and distribution patterns of aquatic organism, including non‐intrusive monitoring of fish migrations and behaviour. In this study, a high frequency acoustic camera (DIDSON‐LR, 1.2 MHz, 0.7 MHz) and a portable split‐beam scientific echo sounder (Simrad EY60, 200 kHz) collected acoustic data on 192 and 157 individuals within 24 hr (19–20 April 2011) in the Mituo reach of the Yangtze River, China. Mean fish lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The measurement accuracy of the imaging sonars in these setups is not as well tested, but the measurements have been compared between low-frequency DIDSON and other methods. Lin et al (2016) used ranges up to 30 m and found that the average DIDSON-measured fish size was similar to the average length of fish in a drift gill net survey. Lilja, Romakkaniemi, et al (2010) compared the size distributions produced from long-range (up to 80 m) DIDSON and angling catch size distribution, and concluded that the DIDSON lengths were approximately 5-10 cm shorter than the true lengths of the fish.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…The measurement accuracy of the imaging sonars in these setups is not as well tested, but the measurements have been compared between low-frequency DIDSON and other methods. Lin et al (2016) used ranges up to 30 m and found that the average DIDSON-measured fish size was similar to the average length of fish in a drift gill net survey. Lilja, Romakkaniemi, et al (2010) compared the size distributions produced from long-range (up to 80 m) DIDSON and angling catch size distribution, and concluded that the DIDSON lengths were approximately 5-10 cm shorter than the true lengths of the fish.…”
Section: Introductionmentioning
confidence: 82%
“…Lin et al . (2016) used ranges up to 30 m and found that the average DIDSON‐measured fish size was similar to the average length of fish in a drift gill net survey. Lilja, Romakkaniemi, et al .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Effective methods for underwater imaging are absolutely vital in retrieving valuable data. Typical methods include stereo vision [13], laser-based systems [15] [3], or acoustic-based systems [9]. These methods can be computationally complex and require intricate computer vision algorithms.…”
Section: Introductionmentioning
confidence: 99%